Is there a place for forgiveness and discomforting pedagogies in the foreign language classroom in higher education? - Porto, Melina (2019)
This article describes a project in which university language students communicated across the globe to address a topic of human rights violations. The aim of the article is to answer the question of whether there is a place in language education for forgiveness and discomforting pedagogies. This focus is new in the field. It begins with an overview of intercultural citizenship education, followed by the pedagogical intervention and case study. It continues with a description of theoretical developments in forgiveness and discomforting pedagogies and provides an analysis of the data from the project with these lenses. Findings indicate that students displayed varying forms of emotional investment as they mediated interculturally with their interlocutors and the ghosts of those who suffered from human rights abuse in the past. The research demonstrates that forgiveness and discomforting pedagogies do have a place in language teaching when combined with intercultural citizenship education.